Exploring the potential of carbocisteine loaded microparticulate system by using ccd model for the treatment of respiratory infections - Rane, Bhushan R.; Gavit, Mayur R; Patil, Vaibhav L; Mhatre, Nandini R; Jain, Ashish S (Journal of Applied Pharmaceutical Research, 2024)
Background: Multi-particulate drug delivery systems (microbeads) deliver drugs over an extended period, distributing them evenly throughout the gastrointestinal tract and minimizing local irritation. Microbeads are small, solid, free-flowing particulate carriers that contain drug particles that have been dispersed and are either crystalline in solution. Aim: The present work explores the potential of the carbocisteine-loaded floating microparticulate drug delivery system. Methodology: Floating microbeads were prepared using the ionotropic gelation method and optimized using Central Composite Design. Result and discussion: Floating microbeads of prepared carbocisteine were evaluated for the FTIR study, which reveals no interaction between the drug and other excipients. Buoyancy time, drug content, particle size, and % drug release were also characterized; it found that drug release was 90.24 %, up to 17 hours, 250 to 220 µm, and drug content 96.67%, respectively, for the optimized batch. An accelerated stability study was performed, showing that the formulation was stable. Floating microparticulate drugs were prepared, and batch B-3 was optimized based on in-vitro buoyancy and release patterns. The floating ability of the beads was observed visually for 10 to 17 hr, and an increase in polymer concentration decreased the swelling of the beads. Conclusion: The results obtained from the formulation batch B-3 show good results for all the parameters tested. Floating microbeads could be the best possible approach to deliver drugs with the benefit of reduced dosing frequency